2013
DOI: 10.1103/physrevb.88.134423
|View full text |Cite
|
Sign up to set email alerts
|

Local and chemical environment dependence of the magnetic properties of CoRh core-shell nanoparticles

Abstract: The ground-state magnetic properties of Co x Rh 1−x nanoparticles having sizes in the range of 0.8-2 nm (N = 43 and 273 atoms) and Co concentrations x ≈ 0, 0.25, 0.5, 0.75, and 1 are investigated in the framework of density-functional theory by using a fixed-moment method. Electron correlation effects are explored by comparing the results of the local spin-density and generalized-gradient approximations to the exchange and correlation functional. The role of chemical order on the magnetic behavior is investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 73 publications
0
5
0
Order By: Relevance
“…On the one hand, the particles can appear in a variety of geometries with or without crystalline ordering . On the other hand, variations in the composition can result in qualitatively different chemical patterns, including core–shell and multishell structures. The combination of both these degrees of freedom turns the sampling of the energy landscape into a formidable task, provoking an active field of research.…”
Section: Introductionmentioning
confidence: 99%
“…On the one hand, the particles can appear in a variety of geometries with or without crystalline ordering . On the other hand, variations in the composition can result in qualitatively different chemical patterns, including core–shell and multishell structures. The combination of both these degrees of freedom turns the sampling of the energy landscape into a formidable task, provoking an active field of research.…”
Section: Introductionmentioning
confidence: 99%
“…79 In the case of Rh-core NPs, the Co moments are largest at the cluster surface (9 l 15) and decrease slightly at the CoRh interface. This holds as long as the concentrations are comparable and the Rh content is not very large.…”
Section: Ferh Corh and Copt Alloy Clustersmentioning
confidence: 95%
“…Another way to induce magnetism is the formation of intermetallics cores of 3 d /4 d and 3 d /5 d elements. Recent experiments and theoretical studies , on CoRh nanoparticles have found not only large Co and sizable Rh moments (despite the fact that Rh is paramagnetic in the bulk) but also strong spin orbit coupling and magnetic anisotropy.…”
Section: Introductionmentioning
confidence: 99%